2022
DOI: 10.1177/19458924221105933
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vidian Neurectomy and Posterior Nasal Neurectomy in the Management of Nonallergic Rhinitis: A Systematic Review

Abstract: Background Nonallergic rhinitis (NAR) is characterized by rhinorrhea, nasal obstruction, and sneezing, in the absence of systemic sensitization to allergens. For cases refractory to medical therapy and conservative surgical interventions, more targeted procedures, such as endoscopic vidian neurectomy (EVN) and posterior nasal neurectomy (PNN), including surgical (SPNN) and cryoablative (CPNN) methods, may reduce symptoms of NAR. Objective The purpose of this study was to compare the efficacy, side effect profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…Cryotherapy has been trialed in the management of chronic rhinitis since the last quarter of the 20th century, and Kompelli et al's 42 2018 qualitative systematic review chronicles how modalities in administering cryotherapy for PNN ablation have evolved over the decades. Indeed, Senanayake et al 43 found cyroablative techniques to be of similar efficacy in treating patients with chronic rhinitis when compared to vidian neurectomy, highlighting the potential for this treatment modality. The present systematic review marks the first attempt to gather and synthesize the findings of all published articles on the efficacy of using a recently available cryotherapy device in the management of chronic rhinitis for both 1- and 3-month time points.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy has been trialed in the management of chronic rhinitis since the last quarter of the 20th century, and Kompelli et al's 42 2018 qualitative systematic review chronicles how modalities in administering cryotherapy for PNN ablation have evolved over the decades. Indeed, Senanayake et al 43 found cyroablative techniques to be of similar efficacy in treating patients with chronic rhinitis when compared to vidian neurectomy, highlighting the potential for this treatment modality. The present systematic review marks the first attempt to gather and synthesize the findings of all published articles on the efficacy of using a recently available cryotherapy device in the management of chronic rhinitis for both 1- and 3-month time points.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review looked at PNN in the context of non-allergic rhinitis along with other treatments; cryoablative PNN and endoscopic vidian neurectomy. 34 In total, 50 of their patients included underwent PNN. They found epistaxis as a complication in 6% of PNN and no patients had dry eye or paraesthesia as a complication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review looked at PNN in the context of non‐allergic rhinitis along with other treatments; cryoablative PNN and endoscopic vidian neurectomy 34 . In total, 50 of their patients included underwent PNN.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on surgical interventions for rhinitis have shown success with posterior nasal nerve (PNN) cryoablation, 3 radiofrequency, 4 or endoscopic posterior nasal neurectomy (EPNN) 2,3 . These interventions remove postganglionic parasympathetic nasal innervation, which helps avoid endoscopic vidian neurectomy (EVN)‐related complications like xerophthalmia and facial/palatal hypesthesia 3,5 …”
Section: Introductionmentioning
confidence: 99%